The Effectiveness of the Problem Based Learning Model on the Social Arithmetic Learning Outcomes of Students at SMP Negeri 1 Sigi - Rahmah Rizki Anugraini; Rahma Nasir; Muhammad Fachri B. Paloloang; Mustamin Idris (FKIP - Universitas Riau, 2026)
This study aims to determine the effectiveness of implementing the Problem Based Learning (PBL) model on student learning outcomes in the Social Arithmetic subject at Sigi State Junior High School 1. This study uses a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research sample consisted of two classes: an experimental class that used the PBL model and a control class that used direct instruction. The research instruments consisted of essay tests (pretest and posttest) that had been validated by experts. Data analysis was conducted using descriptive and inferential statistics, including normality tests, homogeneity tests, independent t-tests, and N-Gain calculations. The results showed that the average posttest score of the experimental class (81.25) was higher than that of the control class (32.16). The hypothesis test results indicated a significance value of 0.001 < 0.05, meaning there was a significant difference between the two groups. Furthermore, the N-Gain value for the experimental class was 0.78 (high category), while that for the control class was 0.20 (low category). This indicates that the Problem Based Learning (PBL) model is more effective in improving student learning outcomes than direct instruction. Thus, the PBL model has been proven effective in enhancing students’ understanding and learning outcomes in Social Arithmetic.